KEBIJAKAN POLSEK TIGADOLOK DALAM MEMBERANTAS PERJUDIAN DI KECAMATAN DOLOK PANRIBUAN - Mitra Bakara; Eka Magdalena; Nico Alfredho Sidabutar; Theresia Simatupang (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2019)
Gambling is every game that bases the hope for a win generally depends only on luck. The expectation will increase because of intelligence and custom players. One area that many people commit the crime of gambling is Tigadolok police station area. The problem discussed in this journal is, how the role of the government in tackling was gambling in Tigadolok, what factors caused the people to commit the crime of gambling, how the policy of Tigadolok police station police forces tried to tackle gambling in Tigadolok. The method of research in writing this journal was empirical and normative legal research, which basically focused on research in the field and positive legal norms in the form of legislation relating to the cases in the study the mechanism of the police in combating gambling. The results showed that there was a gambling criminal case in the territory of the Tigadolok police station, with the number of cases from the year of 2013- 2018 as many as 20 cases. The conclusions were that many efforts done in combating the disease pathology among them was through awareness about the laws governing the crime of gambling, and the main factor for the people committed the crime of gambling was the economic factors where people think that with gambling they could earn additional money for the family income, while police conduct the socialization of Bhayangkara Public Order and Safety Trustees (BABINKAMTIBMAS)